1998
DOI: 10.1042/cs19970303
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the development of renal hypertension in male and female rats

Abstract: 1. The objective of this study was to determine the influence of gender on the development of renal hypertension in Sprague-Dawley rats using the Goldblatt two-kidney, one-clip (2K1C) model. In addition, this study examined the effect of ovariectomy upon the development of hypertension in female rats.2. At 10 weeks of age, male, intact female and ovariectomized female rats underwent clipping of the right renal artery or sham operation. Tail-cuff plethysmography was used to monitor the systolic blood pressure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
1
12
1
Order By: Relevance
“…Many studies have demonstrated that estrogen replacement therapy reduces the risk of cardiovascular disease in postmenopausal women (2). Animal studies also demonstrate gender differences in the development of cardiovascular diseases (3)(4)(5). Thus, circulating endogenous estrogen is proposed to protect against cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that estrogen replacement therapy reduces the risk of cardiovascular disease in postmenopausal women (2). Animal studies also demonstrate gender differences in the development of cardiovascular diseases (3)(4)(5). Thus, circulating endogenous estrogen is proposed to protect against cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast some authors found no change in the weight of the clipped kidney, while they also found an increase in the contralateral kidney [14,15]. Sham-operated rats showed as expected no difference in kidney weight [16,17]. …”
Section: Discussionmentioning
confidence: 98%
“…To our knowledge, only 1 study using 2K1C hypertensive rats has analyzed estrous cyclicity and suggests a similar distribution of cycle stages between 2K1C hypertensive and normotensive female rats. 27 However, this assumption was based on the collection of the vaginal smears only at the completion of the study and based on the observation that all stages of the estrous cycle were represented at that point. Because of our daily checks of estrous cyclicity, we believe that the data presented here provide a more comprehensive look at estrous cycling in the 2K1C model.…”
Section: Hypertension and Estrous Cyclementioning
confidence: 99%